The Effect of Non Performing Financing (NPF) and Earning Asset Quality (KAP) on Return On Assets (ROA) at PT. Bank Rakyat Indonesia Syariah, Tbk 2009-2018 - nur haliza; nofinawati nofinawati; damri batubara; nando fahrizal (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Return On Assets (ROA) is a ratio used to determine the bank's ability to generate profits. The problem in this research is that there is a phenomenon that is not in accordance with the theory. Where, in 2011 the fourth quarter of Non Performing Financing (NPF) decreased accompanied by a decrease in the value of Return On Assets (ROA), as well as Earning Asset Quality (KAP) increased but was not followed by an increase in Return On Assets (ROA). This research is a quantitative research, with the research location at PT. Bank Rakyat Indonesia Syariah, Tbk using secondary data as many as 40 samples in the form of quarterly consolidated financial statements obtained from the website www.ojk.go.id. Analysis of the data used is multiple linear regression test, classic assumption test, coefficient of determination (R2), as well as t test and F test. The results of the partial study (t test) show that Non Performing Financing (NPF) has a significant effect on return. On Assets (ROA), as evidenced by tcount ttable (2.464 2.026) with a significance level of 0.019 0.05, and Earning Asset Quality (KAP) has a significant effect on Return On Assets (ROA), as evidenced by - tcount -ttable that is (-3.385-2.026) with a significance level of 0.002 0.05. Meanwhile, simultaneously Non-Performing Financing (NPF) and Earning Asset Quality (KAP) have a significant effect on Return On Assets (ROA) as evidenced by Fcount Ftable (8.981 3.25) with a significant level of 0.001 0.05.The Effect of Non Performing Financing (NPF) and Earning Asset Quality (KAP) on Return On Assets (ROA) at PT. Bank Rakyat Indonesia Syariah, Tbk 2009-2018